Handbook of reading research, Volume V - Moje, Elizabeth B.; Kamil, Michael L. (Routledge, 2020)
"The Handbook of Reading Research is the research handbook for the field. Each volume has come to define the field for the period of time it covers. Volume IV follows in this tradition. To identify the dominant themes, topics, and developments in the field, the editors surveyed reading research studies and reading policy trends since the year 2000. when Volume III was published. As in previous volumes, the focus is on reading research, rather than a range of literate practices. When taken as a set, the four volumes provide a definitive history of reading research. Volume IV brings the field authoritatively and comprehensively up-to-date."--Back cover